106k views
3 votes
5a+12 = 9A-12

Can anybody help me ?

2 Answers

5 votes

Answer:

a=6

Explanation:

5x+12=9x-12

5x+12-12=9x-12-12

5x=9x-24

5x-9x=9x-24-9x

-4x=-24

-24/-4

x=6

User Imdibiji
by
6.2k points
5 votes

Answer: 12 + 5a = 9a + -12

Reorder the terms:

12 + 5a = -12 + 9a

Solving

12 + 5a = -12 + 9a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-9a' to each side of the equation.

12 + 5a + -9a = -12 + 9a + -9a

Combine like terms: 5a + -9a = -4a

12 + -4a = -12 + 9a + -9a

Combine like terms: 9a + -9a = 0

12 + -4a = -12 + 0

12 + -4a = -12

Add '-12' to each side of the equation.

12 + -12 + -4a = -12 + -12

Combine like terms: 12 + -12 = 0

0 + -4a = -12 + -12

-4a = -12 + -12

Combine like terms: -12 + -12 = -24

-4a = -24

Divide each side by '-4'.

a = 6

Simplifying

a = 6

Step-by-step explanation: found it off of google

User Manxing
by
6.4k points